Dr. Halil Ibrahim Arpa and Prof. Dr. Sabelo Ndlovu Gatsheni on Coloniality of Knowledge - Arpa, Halil Ibrahim; Ndlovu-Gatsheni, Sabelo (Cluster Conversations, 2024)
In this latest episode of the Cluster Conversations Prof. Dr. Sabelo Ndlovu Gatsheni talks with associated fellow Dr. Halil Ibrahim Arpa about his research project entitled “Decolonial Hi/stories: Literary Subversion of Colonial and Post-colonial Historiographies”. In this project, Arpa scrutinizes the coloniality of knowledge against Black and Islamic communities in the Global North and alternative epistemologies to the crisis of modernity in the Global South. Arpa joins the Cluster on a scholarship funded by TÜBITAK (The Scientific and Technological Research Council of Türkiye).